Karakterisasi Pasir Pantai Citra Kabupaten Sukamara Menggunakan XRF dan XRD - Hariyanto, Budi; M. Panggabean, Lady; Hakim, Luqman (Jurnal Jejaring Matematika dan Sains, 2021)
Analysis of the elemental, oxide compounds, and phases composition of Citra beach sand, Sukamara Regency, was successfully carried out. The identification process of elemental and oxide compounds composition used XRF, while the phase identification used XRD analysis. XRF analysis shows that Si and SiO2 dominate the elemental and oxide compound composition by 95,6% and 98,1%, respectively. In addition, the qualitative analysis of the XRD pattern shows that the SiO2 in the Citra beach sand is quartz. These results provide information that Citra beach sand has excellent potential as SiO2 sources.